“It has worked well despite the circumstances” – a study on student social relations and well-being during the pandemic - Fjelkner, Annika; Roxå, Torgny; Warfvinge, Per (Högre utbildning, 2021)
Students’ possibilities to interact with peers have reduced drastically during the emergency transition to online teaching due to the Covid-19 pandemic. Students report on decreased motivation and other study related issues; hence, there is a need to better understand the effects of decreased interaction. The aim of the present exploratory study was to document changes in student networks, in relation to perceptions of connectedness, study outcome and well-being in two different settings. An ad hoc online survey (n = 97) was distributed among students from one research-intensive and one teaching-intensive university where many students commute. Results showed that student social networks defoliated from the outside-in and left students with an inner circle of students they shared multiplex relations with. Students who had lost more working and multiplex relations also reported a decline in well-being. The main contribution of this study is the visualization of how networks became fragmented, and how the experience of this differed depending on type of study context. These findings may have implications for a post-Covid organisation of higher education.